A parametric analysis of the nonlinear dynamics of bistable vibration-based piezoelectric energy harvesters. (April 2021) - Costa, Luã Guedes; Monteiro, Luciana Loureiro da Silva; Pacheco, Pedro Manuel Calas Lopes; Savi, Marcelo Amorim
Piezoelectric materials exhibit electromechanical coupling properties and have been gained importance over the last few decades due to their broad range of applications. Vibration-based energy harvesting systems have been proposed using the direct piezoelectric effect by converting mechanical into electrical energy. Although the great relevance of these systems, performance enhancement strategies are essential to improve the applicability of these system and have been studied substantially. This work addresses a numerical investigation of the influence of cubic polynomial nonlinearities in energy harvesting systems considering a bistable structure subjected to harmonic excitation. A deep parametric analysis is carried out employing nonlinear dynamics tools. Results show complex dynamical behaviors associated with the trigger of inter-well motion. Electrical power output and efficiency are monitored in order to evaluate the configurations associated with best system performances.